2016
DOI: 10.1177/009164711604400403
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Study Findings of an Intensive Outpatient Program for Missionaries and Clergy

Abstract: This article reports the findings of an outcome study done at ALONGSIDE, a counseling-focused retreat center that offers three-week intensive outpatient programs for Christian leaders, the majority of whom are missionaries. Repeated measures research utilized the Outcome Questionnaire - 45.2 (OQ-45.2) to explore whether or not clients participating in the three-week intensive outpatient program realized significant clinical progress and whether or not therapeutic gains were retained after the conclusion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…These findings are visually represented in Figure 1. Table 1 compares the mean OQ-45.2 scores over time from this analysis with those of Jensma (2016). Thus, the proper followup data for comparison purposes revealed that three months after treatment, OQ-45.2 means for Link Care's participants maintained very similar symptom patterns for those in both treatment duration groups, with absolute reductions quite analogous to those of Jensma's (2016) participants.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…These findings are visually represented in Figure 1. Table 1 compares the mean OQ-45.2 scores over time from this analysis with those of Jensma (2016). Thus, the proper followup data for comparison purposes revealed that three months after treatment, OQ-45.2 means for Link Care's participants maintained very similar symptom patterns for those in both treatment duration groups, with absolute reductions quite analogous to those of Jensma's (2016) participants.…”
mentioning
confidence: 82%
“…I was initially pleased to see Jensma's (2016) research suggesting the effectiveness of Alongside's intensive outpatient psychotherapy (IOP) program. Clearly, empirical evidence of an IOP program's therapeutic value is required if the costs of such programs are to be justified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Rosik's (2017) response to my previous article (Jensma, 2016), he indicates that I made an unfortunate comparison between his earlier study (Rosik, 2011) and the outcome study in my article. I agree that such a comparison would be "apples and oranges"-as he calls it-and inappropriate.…”
mentioning
confidence: 99%
“…The purpose of my article (Jensma, 2016) was to present the results of the outcome study done at ALONGSIDE, which indicates that clients see significant progress in our three-week IOP and that the progress remains three months post-treatment. The purpose of the article was to address the question, "Is ALONGSIDE's program effective in the first place, and does the effectiveness of ALONGSIDE's threeweek program endure?"…”
mentioning
confidence: 99%